2023
DOI: 10.3389/frsus.2023.1205680
|View full text |Cite
|
Sign up to set email alerts
|

Promoting sustainability competency and self-efficacy in class teacher education

Roosa Karvonen,
Ilkka Ratinen,
Ulla Kemi

Abstract: There is an urgent need for a global sustainability transition. This change needs to be cultural and transform both our actions and the values on which we base our decision-making. Sustainability transition requires concentrating on future generations as well as on the people teaching them because class teachers have an impact on their pupils' knowledge, skills, values, and attitudes. Therefore, class teachers need new competency to make sustainability transformation in schools happen. Teachers also need to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…According to the model proposed by Baumer and Kunder (2013) [26], competence development is facilitated through a context that ensures, amongst others, practical relevance for the planning; implementation and evaluation of teaching about sustainability; the ability to be contextualized in a theoretical framework; and discussion of teachability and learnability of the described outcomes. The model of pedagogical action competence is characterized as a model that reflects a rather narrow understanding of competence, as it is conceptualized as profession-specific (i.e., specific for school teachers) and domain-specific (i.e., PE, science, or SE) [27] (p. 4).…”
Section: Preparing Competent Educatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the model proposed by Baumer and Kunder (2013) [26], competence development is facilitated through a context that ensures, amongst others, practical relevance for the planning; implementation and evaluation of teaching about sustainability; the ability to be contextualized in a theoretical framework; and discussion of teachability and learnability of the described outcomes. The model of pedagogical action competence is characterized as a model that reflects a rather narrow understanding of competence, as it is conceptualized as profession-specific (i.e., specific for school teachers) and domain-specific (i.e., PE, science, or SE) [27] (p. 4).…”
Section: Preparing Competent Educatorsmentioning
confidence: 99%
“…Preservice teachers' self-efficacy in sustainability education significantly affects their ability to teach about sustainability in class. A study by Karvonen, Ratinen, and Kemi (2023) [27] found that self-efficacy beliefs, particularly in teaching values, ethics, and systems thinking, are crucial for enhancing preservice teachers' sustainability competency. The study emphasized the interconnectedness of self-efficacy beliefs and sustainability competency, advocating for a focused approach in teacher education that addresses both these aspects.…”
Section: Preparing Competent Educatorsmentioning
confidence: 99%